2008
DOI: 10.1007/s11255-008-9481-1
|View full text |Cite
|
Sign up to set email alerts
|

Pupillometric assessment of autonomic nervous system in children with functional enuresis

Abstract: Functional enuresis is defined as repeated voiding of urine into bed or clothes in children after 5 years of age following the exclusion of major somatic diseases. Autonomic nervous system dysregulation has been proposed as a pathophysiologic mechanism in the etiopathogenesis. The objective of this study was to evaluate autonomic nervous system functions with pupil diameter measurement in enuretic children. The study group consisted of 17 children with functional enuresis (ten boys, seven girls), and the contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…It provides precise measurements of pupil size under different lighting conditions [19]. Pupillometry by OPD may also provide relevant information on the autonomic nervous system [20]. We found that pupil size in smokers was larger than nonsmokers in photopic conditions.…”
Section: Discussionmentioning
confidence: 78%
“…It provides precise measurements of pupil size under different lighting conditions [19]. Pupillometry by OPD may also provide relevant information on the autonomic nervous system [20]. We found that pupil size in smokers was larger than nonsmokers in photopic conditions.…”
Section: Discussionmentioning
confidence: 78%
“…Pupillometry offers noninvasive, rapid, and objective measurements of pupillary function; these measurements serve as an ideal instrument to quantify ophthalmologic-specific ANSD. Pupillometry has been successfully used to evaluate ANSD in autonomic neuropathies (14)(15)(16), pediatric enuresis (17), heart failure (18), and familial dysautonomia (19) and has the potential for use in other pediatric disorders of respiratory and autonomic dysregulation. Although multiple factors can influence pupil diameter and response, with standardized conditions and intact afferent pathways, pupillometry allows for insight into efferent ANS pathways (14).…”
Section: Ongenital Central Hypoventilation Syndrome (Cchs) Ismentioning
confidence: 99%
“…The symptom score with Akbal's questionnaire was median 17 minimum 9, maximum 26 and mean score was 16.5 in the study group. The cutoff value is 8.5 in Akbal's questionnaire for lower urinary tract dysfunction .…”
Section: Resultsmentioning
confidence: 79%
“…Effectiveness of anticholinergic medications in enuretic children supports this hypothesis. Autonomic system and enuresis studies have been carried out in children with monosymptomatic nocturnal enuresis (MNE) . But study concerning autonomic dysfunction in children with OAB have not yet been published.…”
Section: Discussionmentioning
confidence: 99%